All-carbon electronic devices fabricated by directly grown single-walled carbon nanotubes on reduced graphene oxide electrodes - Boey, Freddy Yin Chiang (2012)
A simple method for fabrication of all carbon CNT-rGO devices was developed, where the individual long-aligned SWCNT directly grew by CVD to connect with rGO electrodes scratched by non-metal objects.